Modulating Alginate Hydrogels for Improved Biological Performance as Cellular 3D Microenvironments - Neves, Mariana Isabel; Moroni, Lorenzo; Barrias, Cristina Carvalho (Frontiers in Bioengineering and Biotechnology, 2020)
The rational choice and design of biomaterials for biomedical applications is crucial for successful in vitro and in vivo strategies, ultimately dictating their performance and potential clinical applications. Alginate, a marine-derived polysaccharide obtained from seaweeds, is one of the most widely used polymers in the biomedical field, particularly to build three dimensional (3D) systems for in vitro culture and in vivo delivery of cells. Despite their biocompatibility, alginate hydrogels often require modifications to improve their biological activity, namely via inclusion of mammalian cell-interactive domains and fine-tuning of mechanical properties. These modifications enable the addition of new features for greater versatility and control over alginate-based systems, extending the plethora of applications and procedures where they can be used. Additionally, hybrid systems based on alginate combination with other components can also be explored to improve the mimicry of extracellular microenvironments and their dynamics. This review provides an overview on alginate properties and current clinical applications, along with different strategies that have been reported to improve alginate hydrogels performance as 3D matrices and 4D dynamic systems.